2018
DOI: 10.3389/fpsyg.2018.00132
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction, Organizational Commitment and Job Involvement: The Mediating Role of Job Involvement

Abstract: We conducted an empirical study aimed at identifying and quantifying the relationship between work characteristics, organizational commitment, job satisfaction, job involvement and organizational policies and procedures in the transition economy of Serbia, South Eastern Europe. The study, which included 566 persons, employed by 8 companies, revealed that existing models of work motivation need to be adapted to fit the empirical data, resulting in a revised research model elaborated in the paper. In the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(158 citation statements)
references
References 58 publications
(67 reference statements)
8
145
0
5
Order By: Relevance
“…In line with the conceptualization of SET, it posits that job satisfaction facilitates employees' commitment toward their organization. The result is also found consistent with prior studies in other settings (Ćulibrk et al, 2018;Lambert et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with the conceptualization of SET, it posits that job satisfaction facilitates employees' commitment toward their organization. The result is also found consistent with prior studies in other settings (Ćulibrk et al, 2018;Lambert et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The higher social exchange ensures stronger employees' contribution and commitment, which results in better individual and team performance. The stronger relationship between job satisfaction and employees' loyalty (Ćulibrk et al, 2018;Mihaela, 2014;Peng, 2014) makes the workforce happier and more productive (Edwards et al, 2008). When employees notice that their perceived organizational support gets attention, Aslan, Shaukat, Ahmed, Shah, and Mahfar (2014) found their (employees) reciprocal consequent positive outcomes in the form of commitment, satisfaction and citizenship behaviors have been improved (Ababneh & Hackett, 2019;Lambert et al, 2018).…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Job involvement was found to play a mediating role in the relationship between organizational commitment and job performance (Kappagoda, ) and between job characteristics and organizational citizenship behavior (Chen & Chiu, ). A recent study found that job involvement partially mediated the relationship between job satisfaction and organizational commitment, and that job satisfaction had a direct impact on organizational commitment (Ćulibrk, Delić, Mitrović, & Ćulibrk, ). Additionally, job involvement also mediates the relationship between a manager's good character and employees’ organizational affective commitment (Ghassemi, Isfahani, Abbaspour, & Farhanghi, ).…”
Section: The Aspects Of a Learning Organizationmentioning
confidence: 99%
“…Employee commitment is important and plat crucial role in organizational success. Strong commitment is correlated with organizational citizenship, job satisfaction, job performance and employee retention (Ćulibrk, Delić, Mitrović, & Ćulibrk, 2018;Hafiz, 2017;Quratulain, Khan, Crawshaw, Arain, & Hameed, 2018). According to Lok & Crawford (2001), employees' commitment is viewed from behavioural and attitudinal perspectives.…”
Section: Concept Of Employee Commitmentmentioning
confidence: 99%